Distribution dynamics of arsenic and silicon in different parts of rice grown under field conditions. Issue 5 (2nd September 2020) - Akahane, Ikuko; Suda, Aomi; Ishikawa, Satoru; Abe, Tadashi; Baba, Koji; Furuya, Manami; Yamaguchi, Noriko
ABSTRACT: Rice ( Oryza sativa L.) grown in flooded paddy fields is a large contributor of inorganic arsenic (As) to human diets. The absorption pathway of arsenite via rice roots is known to be similar to that of silicon (Si). However, the spatiotemporal dynamics of As and Si in the aboveground parts of rice plants at different growth stages are not yet fully understood. In this study, we aimed to compare the distribution and accumulation patterns of As and Si in different organs of rice plants grown under field conditions. Rice was cultivated in a field under flooded conditions for 3 weeks before and after heading. Rice hills were sampled every 2 to 13 days and separated into leaf blades excluding the flag leaf, flag leaf, stems, node I, and panicle. Then, the dry weight of each organ and its concentrations of As and Si were determined. The contents of As and Si in each organ of rice increased with growth. In the flag leaves, the As and Si contents continuously increased even after the dry weight increase reached a plateau, and their accumulation patterns were similar. In contrast, the contents of As and Si in the panicle increased with increasing dry weight, and their accumulation patterns were different since Si was preferentially transported to the husk, whereas As was distributed in both the grain and husk. At maturity, 17 and 37% of As and Si, respectively, in the aboveground part were distributed in the panicle, suggesting that As transport to the panicle was restricted compared with that of Si. Arsenic was substantially accumulated in node I, whereas Si was not. In conclusion, the accumulation characteristics of As and Si in rice grains were different because As transport to the panicle was suppressed due to accumulation in node I, although Si was efficiently transported toward the panicle.